APPLICATION OF OPERATIONAL MANAGEMENT IN CREATIVE INDUSTRIES IN THE DIGITAL ERA - Imam Wibowo (INFOKUM, 2022)
This industry has grown rapidly and become a major pillar in the global economy, with dynamic changes in technology and ever-growing market demand. This research aims to investigate and analyze effective operational management practices in the context of creative industries in the digital era. This research uses a qualitative approach with descriptive methods. The research results show that the implementation of operational management that is responsive to change, supported by technology and automation systems, has a positive impact in increasing the efficiency of the creative and digital industries. Managing creativity as a key asset, together with holistic skills training, has been proven to make a significant contribution to innovation in products and services. Data analysis is becoming a valuable tool in forecasting market trends and supporting data-driven decisions for sustainable growth. Additionally, partnerships with technology companies and educational institutions open new opportunities for collaboration, access additional resources, and stimulate innovation. Thus, the research results confirm that a holistic approach to operational management, which combines creative and operational aspects, plays a key role in creating an environment that supports sustainable growth and excellence in creative and digital industries.